Bacterial colonization of psoriasis plaques. Is it relevant? - Eva Marcus; Diana Demmler; Andreas Rudolph; Matthias Fischer (PAGEPress Publications, 2011)
Bacterial colonization was investigated retrospectively in patients with plaque psoriasis (n=98 inpatient treatments, n=73 patients). At least one pathogen was found in 46% of all cases. Staphylococcus aureus was the most frequent bacterium. Bacterial colonization of psoriasis plaques could be relevant in individual cases.